The Influence of Leadership, Supervision And Work Discipline on Teacher Performance at Talitakum Medan Private Junior High School - Elsa Gultom; Yohny Anwar; Kiki farida ferine (International Journal of Society and Law, 2024)
This research was conducted at Talitakum Private Junior High School in Medan with the aim of finding out how much the influence of Leadership, Supervision and Work Discipline partially and simultaneously on teacher performance. The population in this study is all employees of Talitakum Medan Private Junior High School totaling 34 people with independent variables of Leadership, Supervision and Work Discipline while teacher performance is the dependent variable. The method used is a data analysis method using multiple linear regression analysis techniques, classical assumption tests and hypothesis tests. The results of the regression test showed that 58.6% of performance factors could be explained by leadership, supervision and work discipline while the remaining 41.4% were explained by other factors that were not examined in this study such as work motivation, position, intensive, training and so on. Meanwhile, the results of the f test showed that simultaneously leadership, supervision and work discipline together had a significant effect on teacher performance with the results of the tcount analysis (28,229) where the table was 2,922. The results of the T test showed that the leadership variable showed the results of the tcount analysis (2,376), the supervision variable showed the results of the tcount analysis (3,935) and the work discipline variable showed the results of the tcount analysis (3,611) where the ttable (1,690). So these three variables have a significant effect on the performance of teachers at Talitakum Private Junior High School in Medan.